Narrativas del padecimiento “mental”: arenas de debate en torno a prácticas sociales y a los valores que las sustentan entre los mayas tzotziles y tzeltales del sur de México - Eroza, Enrique (Revista de Antropología Social, 2008)
Through narrative accounts this paper examines the particular meanings related to two local categories of illness amongst the tzotzil and tzeltal Maya peoples of Southern Mexico, whose symptoms are similar to those of Western concepts of psychiatric disorder. Given the character of the accounts in terms of experiences, both categories are placed within a broader explanatory frame. On the one hand it is made up by ideas associated to divine punishment and witchcraft, which account for a realm of human interaction connecting earthly and spiritual events. On the other hand, by values attached to socio-cultural practices. It is in this scenario where the narratives are placed to reveal the morally contradictory nature of these practices, which becomes evident thorough the ambiguity and variability of stances of those who from particular positions interact with the sufferer.